Shop floor control in smart factories’ era: paths and maturity model - Bueno, Adauto Farias (Universidade Federal de São Carlos, 2022)
Scholars and practitioners have conceived Industry 4.0 as a comprehensive set of emerging technologies clustered in smart technological ecosystems into industrial companies. Since Smart Manufacturing is at the core of this concept, Production Planning and Control (PPC) plays a “brain” role in companies because it can lead them toward Smart Factories. This Doctoral Dissertation aims to investigate the relationships between Industry 4.0’ technologies and the manufacturing industry from a Shop Floor Control/Production Planning and Control function perspective. Firstly, we delimit the relationships between Industry 4.0 and the organizational entity of PPC/SFC from an extensive Systematic Literature Review. Second, we proposed a standard framework to develop maturity models into Industry 4.0’ era. Third, we proposed and designed a focus-area and prescriptive Smart Shop Floor Control Maturity Model (S2FC MM) based on five research iterations from Design Science Research - DSR. Our S2FC MM contains five focus areas comprised of 20 key factors covered by 98 capabilities (maturity matrix). S2FC MM is a progression maturity model with five maturity levels entailing the Industry 4.0-concept. S2FC MM was validated and implemented in a steel manufacturing company.
O controle de chão-de-fábrica na era das fábricas inteligentes: caminhos e modelo de maturidade
Keywords: Industry 4.0; Smart Production Planning and Control; Smart Manufacturing; Maturity Model; Maturity Paths; Artifacts; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO